Economic vulnerability of timber resources to forest fires. - Rodríguez y Silva, Francisco; Molina, Juan Ramón; González-Cabán, Armando; Machuca, Miguel Ángel Herrera; y Silva, Francisco Rodríguez; Molina, Juan Ramón; González-Cabán, Armando; Machuca, Miguel Ángel Herrera (Journal of environmental management, 2012)
The temporal-spatial planning of activities for a territorial fire management program requires knowing the value of forest ecosystems. In this paper we extend to and apply the economic valuation principle to the concept of economic vulnerability and present a methodology for the economic valuation of the forest production ecosystems. The forest vulnerability is analyzed from criteria intrinsically associated to the forest characterization, and to the potential behavior of surface fires. Integrating a mapping process of fire potential and analytical valuation algorithms facilitates the implementation of fire prevention planning. The availability of cartography of economic vulnerability of the forest ecosystems is fundamental for budget optimization, and to help in the decision making process.
Keywords: Conservation of Natural Resources; Conservation of Natural Resources: economics; Decision Making; Economic valuation; Ecosystem; Fire economic losses; Fire prevention planning; Fires; Timber valuation; Trees

Use of an airborne lidar system to model plant species composition and diversity of Mediterranean oak forests. - Simonson, William D; Allen, Harriet D; Coomes, David A (Conservation biology : the journal of the Society for Conservation Biology, 2012)
Airborne lidar is a remote-sensing tool of increasing importance in ecological and conservation research due to its ability to characterize three-dimensional vegetation structure. If different aspects of plant species diversity and composition can be related to vegetation structure, landscape-level assessments of plant communities may be possible. We examined this possibility for Mediterranean oak forests in southern Portugal, which are rich in biological diversity but also threatened. We compared data from a discrete, first-and-last return lidar data set collected for 31 plots of cork oak (Quercus suber) and Algerian oak (Quercus canariensis) forest with field data to test whether lidar can be used to predict the vertical structure of vegetation, diversity of plant species, and community type. Lidar- and field-measured structural data were significantly correlated (up to r= 0.85). Diversity of forest species was significantly associated with lidar-measured vegetation height (R(2) = 0.50, p < 0.001). Clustering and ordination of the species data pointed to the presence of 2 main forest classes that could be discriminated with an accuracy of 89% on the basis of lidar data. Lidar can be applied widely for mapping of habitat and assessments of habitat condition (e.g., in support of the European Species and Habitats Directive [92/43/EEC]). However, particular attention needs to be paid to issues of survey design: density of lidar points and geospatial accuracy of ground-truthing and its timing relative to acquisition of lidar data.
Keywords: Biodiversity; Biological; cluster analysis; Conservation of Natural Resources; Conservation of Natural Resources: methods; Ecosystem; mediterranean oak forest; Models; Portugal; predictive modeling; Quercus; Remote sensing; Remote Sensing Technology; Remote Sensing Technology: methods; Species Specificity; vascular plants

Changes in land cover and vegetation carbon stocks in Andalusia, Southern Spain (1956-2007). - Muñoz-Rojas, M; De la Rosa, D; Zavala, L M; JORDÁN, A; Anaya-Romero, M (The Science of the total environment, 2011)
Land use has significantly changed during the recent decades at global and local scale, while the importance of ecosystems as sources/sinks of C has been highlighted, emphasizing the global impact of land use changes. Land use changes can increase C loss rates which are extremely difficult to reverse, in the short term, opposite to organic carbon (OC) which accumulates in soil in the long-term. The aim of this research is to improve and test methodologies to assess land cover change (LCC) dynamics and temporal and spatial variability in C stored in vegetation at a wide scale. LCCs between 1956 and 2007 in Andalusia (Southern Spain) were selected for this pilot study, assessed by comparison of spatial data from 1956 to 2007 and were reclassified following land cover flows (LCFs) reported in major areas in Europe. Carbon vegetation densities were related to land cover, and C vegetation stocks for 1956 and 2007 were calculated by multiplying C density for each land cover class with land cover areas. The study area has supported important changes during the studied period with significant consequences for vegetation C stocks, mainly due to afforestation and intensification of agriculture, resulting in a total vegetation C stock of 156.08Tg in 2007, with an increase of 17.24Tg since 1956. This study demonstrates the importance of LCC for C sequestration in vegetation from Mediterranean areas, highlighting possible directions for management policies in order to mitigate climate change as well as promoting land conservation. The methodologies and information generated in this project will be a useful basis for designing land management strategies helpful for decision makers.
Keywords: Agriculture; Agriculture: statistics & numerical data; Carbon; Carbon Sequestration; Carbon: analysis; Carbon: metabolism; Cities; Cities: statistics & numerical data; climate change; Conservation of Natural Resources; CORINE Land Cover; Environment; Environmental Monitoring; Land use planning; Plant Development; Plants; Plants: chemistry; Plants: metabolism; Soil Pollutants; Soil Pollutants: analysis; Soil Pollutants: metabolism; Spain; Sustainable land management

Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J.; Soto, Álvaro; Gil, Luis; Soto, Álvaro; Gil, Luis (Annals of Botany, 2009)
Background and Aims Marginal populations of widely distributed species can be of high conservation interest when they hold a significant or unique portion of the genetic diversity of the species. However, such genetic information is frequently lacking. Here the relevance of genetic surveys to develop efficient conservation strategies for such populations is illustrated using cork oak (Quercus suber) from Minorca (Balearic Islands, Spain) as a case study. Cork oak is highly endangered on the island, where no more than 67 individuals live in small, isolated stands in siliceous sites. As a consequence, it was recently granted protected status.Methods Two Bayesian clustering approaches were used to analyse the genetic structure of the Minorcan population, on the basis of nuclear microsatellite data. The different groups within the island were also compared with additional island and continental populations surrounding Minorca.Key Results Very high genetic diversity was found, with values comparable with those observed in continental parts of the species' range. Furthermore, the Minorcan oak stands were highly differentiated from one another and were genetically related to different continental populations of France and Spain.Conclusions The high levels of genetic diversity and inter-stands differentiation make Minorcan cork oak eligible for specific conservation efforts. The relationship of Minorcan stands to different continental populations in France and Spain probably reflects multiple colonization events. However, discrepancy between chloroplast DNA- and nuclear DNA-based groups does not support a simple scenario of recent introduction. Gene exchanges between neighbouring cork oak stands and with holm oak have created specific and exceptional genetic combinations. They also constitute a wide range of potential genetic resources for research on adaptation to new environmental conditions. Conservation guidelines that take into account these findings are provided.
From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)The following values have no corresponding Zotero field: accession-num: 19671575
Keywords: Balearic Islands; cluster analysis; conservation guidelines; Conservation of Natural Resources; Genetic Variation; Geography; marginal populations; Minorca; Nuclear microsatellites; Population Dynamics; Q. ilex (holm oak); Quercus; Quercus suber (cork oak); Quercus: genetics; Soil; Spain; western Mediterranean

Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis; Soto, Álvaro; Gil, Luis (Annals of Botany, 2009)
Background and Aims Marginal populations of widely distributed species can be of high conservation interest when they hold a significant or unique portion of the genetic diversity of the species. However, such genetic information is frequently lacking. Here the relevance of genetic surveys to develop efficient conservation strategies for such populations is illustrated using cork oak (Quercus suber) from Minorca (Balearic Islands, Spain) as a case study. Cork oak is highly endangered on the island, where no more than 67 individuals live in small, isolated stands in siliceous sites. As a consequence, it was recently granted protected status.Methods Two Bayesian clustering approaches were used to analyse the genetic structure of the Minorcan population, on the basis of nuclear microsatellite data. The different groups within the island were also compared with additional island and continental populations surrounding Minorca.Key Results Very high genetic diversity was found, with values comparable with those observed in continental parts of the species' range. Furthermore, the Minorcan oak stands were highly differentiated from one another and were genetically related to different continental populations of France and Spain.Conclusions The high levels of genetic diversity and inter-stands differentiation make Minorcan cork oak eligible for specific conservation efforts. The relationship of Minorcan stands to different continental populations in France and Spain probably reflects multiple colonization events. However, discrepancy between chloroplast DNA- and nuclear DNA-based groups does not support a simple scenario of recent introduction. Gene exchanges between neighbouring cork oak stands and with holm oak have created specific and exceptional genetic combinations. They also constitute a wide range of potential genetic resources for research on adaptation to new environmental conditions. Conservation guidelines that take into account these findings are provided.
From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)
Keywords: Balearic Islands; cluster analysis; conservation guidelines; Conservation of Natural Resources; Genetic Variation; Geography; marginal populations; Minorca; Nuclear microsatellites; Population Dynamics; Q. ilex (holm oak); Quercus; Quercus suber (cork oak); Quercus: genetics; Soil; Spain; western Mediterranean

The influence of linear elements on plant species diversity of Mediterranean rural landscapes: assessment of different indices and statistical approaches. - García del Barrio, J M; Ortega, M; Vázquez De la Cueva, A; Elena-Rosselló, R (Environmental monitoring and assessment, 2006)
This paper mainly aims to study the linear element influence on the estimation of vascular plant species diversity in five Mediterranean landscapes modeled as land cover patch mosaics. These landscapes have several core habitats and a different set of linear elements--habitat edges or ecotones, roads or railways, rivers, streams and hedgerows on farm land--whose plant composition were examined. Secondly, it aims to check plant diversity estimation in Mediterranean landscapes using parametric and non-parametric procedures, with two indices: Species richness and Shannon index. Land cover types and landscape linear elements were identified from aerial photographs. Their spatial information was processed using GIS techniques. Field plots were selected using a stratified sampling design according to relieve and tree density of each habitat type. A 50x20 m2 multi-scale sampling plot was designed for the core habitats and across the main landscape linear elements. Richness and diversity of plant species were estimated by comparing the observed field data to ICE (Incidence-based Coverage Estimator) and ACE (Abundance-based Coverage Estimator) non-parametric estimators. The species density, percentage of unique species, and alpha diversity per plot were significantly higher (p < 0.05) in linear elements than in core habitats. ICE estimate of number of species was 32% higher than of ACE estimate, which did not differ significantly from the observed values. Accumulated species richness in core habitats together with linear elements, were significantly higher than those recorded only in the core habitats in all the landscapes. Conversely, Shannon diversity index did not show significant differences.
Keywords: Biodiversity; Conservation of Natural Resources; Conservation of Natural Resources: statistics & nu; core habitat; diversity; Ecosystem; ecotones; Environmental Monitoring; Environmental Monitoring: methods; Geography; landscape; linear elements; Mediterranean; Mediterranean Region; Plant Development; Poaceae; Poaceae: growth & development; Shannon index; Species richness; Species Specificity; Trees; Trees: growth & development